Flow Characteristic Of Wetpond - Derani, Mohamad Ansar (Universiti Sains Malaysia, 2005)
Water is the most vital source in our life. It has become the nerve of the existence of all living things on earth and it encompasses two – thirds of the earth surface. A system to control these water sources from being polluted or causing annihilation for mankind is much needed. It is important to ensure the stability to be maintained. Hence, on this initiative, a research has been carried out on the methods of controlling water at the source and the result is the Bio-Ecological Drainage System (BIOECODS) system where wetpond is one of the main components in it. In this study, the data on the flow rate at the inlet and outlet of wetpond are accumulated and analyzed to know the capabilities of the pond to function in ensuring that reduction of water flow rate can happen. Data and analysis conducted are very important to produce reference order for the construction of the system at future projects. The results confirm the attenuation effect of the wetpond. For rainfall event less than 3-month ARI, the outflow discharge is almost zero.